PENGARUH=DEBT TO EQUITY RATIO DAN-NET/PROFIT MARGIN-TERHADAP HARGA SAHAM/PERUSAHAAN OTOMOTIF YANG-TERDAFTAR-DI BEI TAHUN 2014 – 2021 - Novita Ika Dyamayanti; Renea Shinta Aminda; Diah Yudhawati (Cross-border, 2023)
Stock price valuation is an investment valuation that is often used by investors to invest because of the many advantages. This research uses quantitative research methods. This research-was conducted to-determine theeffect-of Debt To Equity-Ratio andNet Profit Margin on stock prices. The population in this study were 16 automotive companies listed on the IDX in 2014 – 2021. The research sample used a purposive sampling method to produce 11 suitable companies. The analysis used is-descriptive analysis-and multiple linear analysis. Based on simultaneous testing, it is known thatthe Debt to Equity Ratio and Net Profit-Margin variables simultaneously affect stock prices. While the results of the partial test of the Debt To Equity Ratio variable have-a positive effect onstock prices, while the Net Profit-Margin variable-has no effect onstock prices.